Substance-Free Transitional Housing and Community Corrections in Washington County, Oregon, 2005-2008 - Finigan, Michael ([Verlag nicht ermittelbar], 2013)
The study investigated self-sufficiency, community adjustment, substance use, and criminal recidivism outcomes for substance abusing offenders served through the Washington County (Oregon) Community Corrections Department (WCCC) to document the value-added of providing substance-free transitional housing services. The study addressed the value-added of Oxford House and other transitional housing services to the combination of services offenders receive, and documented the relative costs and benefits of substance-free transitional housing services. Individuals were eligible for the study if they entered Oxford Houses, entered some other form of substance-free transitional housing, or could benefit from, but did not enter, any form of substance-free transitional housing. A total of 356 supervisees were eligible for the study; 301 agreed to participate in baseline interviews, and 238 participated in 12-month follow-up interviews. The study included both interview data collection and administrative records data collection. The research team also collected Housing Data (Part 2) from the housing section of the interviews and Treatment Data (Part 3) from a statewide treatment database.